2017
DOI: 10.4314/tjpr.v16i9.10
|View full text |Cite
|
Sign up to set email alerts
|

MiR-495-3p facilitates colon cancer cell proliferation via Wnt/β-catenin signaling pathway by restraining Wnt inhibitory factor

Abstract: Purpose: To demonstrate whether miR-495-3p promote the occurrence of colon cancer and development of colon cancer stem cells by inhibiting Wnt inhibitory factor (WIF1). Methods: The level of MiRNA and mRNA in cells were tested by real-time polymerase chain reaction (RT-PCR). Cell viability was assessed by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT) assay. Cell spheroid formation was measured by colony assay. Expression protein was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For example, miR-495-3p is sponged by lncRNA NEAT1 to regulate STAT3 expression, resulting in alleviation of septicemia-related inflammatory response (19). Moreover, it is worth noting that miR-495-3p serves as an inhibitory regulator in CRC (20). However, the relationship between LUNAR1 and miR-495-3p, and the specific mechanisms involved remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-495-3p is sponged by lncRNA NEAT1 to regulate STAT3 expression, resulting in alleviation of septicemia-related inflammatory response (19). Moreover, it is worth noting that miR-495-3p serves as an inhibitory regulator in CRC (20). However, the relationship between LUNAR1 and miR-495-3p, and the specific mechanisms involved remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that miR-495-3p inhibits the progression of prostate cancer, colorectal cancer and melanoma [6,20,21]. In contrast, recent study provided important evidence about an oncogenic role of miR-495-3p in colon cancer [7].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al showed that miR-495-3p is downregulated in prostate cancer and regulates migration and invasion in prostate cancer cells by targeting AKT and mTOR transcripts [6]. In contrast, Lin et al analysis revealed that miR-495-3p expression level is elevated in colon tumors and confirmed an oncogenic role for this miRNA exerted by targeting the WIF1 gene, a Wnt/β-catenin signaling pathway inhibitor [7]. The various roles of miR-495 in cancer progression have been reviewed recently by Chen et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted byLi et al (2016), the unusually high expression of miR-665 was also observed in both heart and plasma during heart failure, and the important role miR-665 played in discriminating patients from controls and affecting LVEF had been reported. In addition, we made observations of impaired cardiac function and promoted cell apoptosis when miR-665 had become upregulated.According to a recent study, overexpressing miR-665 was reported to have inhibited the proliferation, migration, and invasion of the vascular smooth muscle cells, with downregulating miR-665 capable of promoting those processes (K Li, Pan, Wang, Liu, & Wang, 2017)…”
mentioning
confidence: 99%